(untitled) (Bangladesh Journal of Anatomy, 2019)
Context: The measurement of lower limb dimensions showed a high success rate in establishing individual identity in terms of sex and stature in various populations. The study was aimed to measure the thigh length, lower leg length, biepicondylar breadth of femur & bimalleolar breadth of Bangladeshi garment workers. Materials and Methods: Sixty male & sixty female aged 20-35 years were enrolled in this study. The anthropometric measurements of the subjects were measured with the help of anthropometric equipment such as digital slide calipers and flexible measuring tape. Results: Male garment workers had higher mean values of lower limb variables (p<0.001). Conclusion: In the present study significantly higher value of anthropometric measurements was found in male Bangladeshi garment workers than female. These results are significant in forensics and orthopedic reconstructive surgery. Bangladesh Journal of Anatomy July 2019, Vol. 17, No. 2, pp. 32-35